Developing a blended learning curriculum using a digital notebook application for a surgical nursing practicum: The ADDIE model - Apichat Kardosod; Kanittha Rattanakanlaya; Lalida Noppakun; Chutima Meechamnan; Rujadhorn Indratula; Sirinard Deechairum (Belitung Raya Foundation, Indonesia, 2023)
Background: The COVID-19 pandemic has presented challenges to nursing practice globally. However, utilizing digital notebook applications to support nursing student practices may be an effective tool for surgical nursing practicum. Objective: This study aimed to design a blended learning curriculum for surgical nursing practicum, utilizing a digital notebook platform. Methods: This study applied the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model to create a blended learning curriculum for surgical nursing practicum, employing the OneNote application platform. The study included three experts and 90 third-year nursing students who evaluated the model. The study was conducted from July 2021 to March 2022 at the Faculty of Nursing, Chiang Mai University, Thailand. Data were analyzed using descriptive statistics. Results: The experts rated the model highly (Mean = 4.33, SD = 0.57). The satisfaction level of the students with the blended learning curriculum using a digital notebook application was also high (Mean = 4.88, SD = 0.31). Conclusion: The blended learning curriculum using a digital notebook application for surgical nursing practicum was satisfactory for learners. The results from this research can be applied in online learning or incorporated into nursing clinical practicum curricula during and even post-pandemic. The study results may also serve as an example or a piece of basic information to further develop an advanced online platform for teaching learning, either in Thailand or globally.